Wysoko wrażliwy uczeń języka obcego – o potencjalnej roli poziomu wrażliwości przetwarzania sensorycznego w kontekście edukacji językowej - Nosidlak, Katarzyna (Neofilolog, 2025)
High sensitivity, a term introduced into both popular and scientific discourse by American psychologist Elaine Aron in the 1990s, refers to individuals who exhibit a high level of so-called sensory processing sensitivity (SPS). These individuals demonstrate increased responsiveness of the nervous system, engage in deep processing of both external and internal stimuli, and show a tendency for more elaborate information processing. Recognizing the potential influence of heightened sensitivity on educational experiences, this article introduces the concept of the highly sensitive language learner (HSLL) to address how high sensitivity potentially affects foreign language acquisition and use. By analysing existing empirical studies, it identifies domains where individuals with high sensitivity may face unique challenges or derive distinct advantages compared to those with lower levels of sensitivity. Based on this, recommendations for educators and practitioners working with HSLLs are also offered.